2018
DOI: 10.1186/s13256-018-1812-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydatidosis of infratemporal fossa with proptosis – an unusual presentation: a case report and review of the literature

Abstract: BackgroundHydatid disease is one of the common zoonotic diseases caused by the larval stage of Echinococcus granulosus. It is endemic in sheep-raising and cattle-raising areas worldwide and humans are an accidental intermediate host following the ingestion of the larvae. Head and neck involvement of echinococcosis is a rare entity and involvement of the infratemporal region is extremely rare even in endemic areas. Only a few cases of hydatid cysts located in the infratemporal fossa have been reported in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Surgery area of brain covering cotton soaked with warm normal saline to prevent spillage in case of rupture. Then, the cyst removes and dura closing watertight, bone flap puts back and patient dresses after wound closure 2,14 . After craniotomy and prior to the incision, the surgical field must be cleaned with scolicidal solution to prevent recurrence because even a minimal spillage can lead to new cysts formation (1 mL of cyst fluid contains 4 000 000 scolices) 15,16 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgery area of brain covering cotton soaked with warm normal saline to prevent spillage in case of rupture. Then, the cyst removes and dura closing watertight, bone flap puts back and patient dresses after wound closure 2,14 . After craniotomy and prior to the incision, the surgical field must be cleaned with scolicidal solution to prevent recurrence because even a minimal spillage can lead to new cysts formation (1 mL of cyst fluid contains 4 000 000 scolices) 15,16 …”
Section: Discussionmentioning
confidence: 99%
“…Then, the cyst removes and dura closing watertight, bone flap puts back and patient dresses after wound closure. 2,14 After craniotomy and prior to the incision, the surgical field must be cleaned with scolicidal solution to prevent recurrence because even a minimal spillage can lead to new cysts formation (1 mL of cyst fluid contains 4 000 000 scolices). 15,16 Albendazole has been used successfully for treatment of hydatid cyst in brain, 17 for prevention of secondary hydatid disease.…”
Section: F I G U R E 1 Preoperation Ct Scan Revealed a Large Cystic Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone hydatid cyst, which mostly affects the spine, accounts for 0.5% to 2.5% of hydatid cyst cases [ 10 , 11 , 28 , 29 ]. The bone hydatid cyst has been reported in 44 patients for 20 years in Iran [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other tissues that are rarely affected by hydatid cysts include the perianal area, infratemporal region, or neck [ 10 , 12 14 ]. It has been shown that the replacement of hydatid cysts in unusual locations might be linked to the parasite genotypes and probably its intragenotypic features [ 15 ].…”
Section: Introductionmentioning
confidence: 99%